العبادات بين التعليل والتعبُّد: مقاربة أصولية - جميلة تلوت (International Institute of Islamic Thought, 2015)
يعدّ إشكال تعليل العبادات من المسائل المختلف فيها قديماً وحديثاً، ويتعزز الإشكال أكثر مع إعلان الشاطبي بأن أحكام الله تعالى تعلل بالمصالح، الأمر الذي يثير السؤال الآتي: كيف يمكن القول إن أحكام العبادات غير معللة، وإن الأصل فيها التعبُّد؟ هذا هو محل الإشكال في البحث، لذلك عملت على مقاربته منهجياً، بدءاً من تحديد المفاهيم، ثم ذكر الخلاف الأصولي في المسألة، وتحرير محل النـزاع وبيان أدلة الآراء، ثم بيان أثر الخلاف في ذلك على الخلاف الفقهي في عدد من المسائل العبادية، وأخيراً اقتراح مداخل التجاوز بانتهاج مقاربة تغلب النظر المقصدي. The rationalization in the Islamic acts of worship is a problematic issue, especially since al-Shāṭibī has proclaimed that all Sharī'ah provisions are rationalized in terms of what is good for people. The question that needs to be answered is: how can it be said that acts of worship are not necessarily rationalized, and that they are based on ritual obedience? The article tries to approach the issue methodologically, starting from defining the concepts, stating the different opinions on the issue, clarifying the heart of the debate, and tracing the effects of this Uṣūlī disagreement on the fiqhī disagreement in a number of worship issues. Finally, the article suggested a maqāsidī approach to go around this problematic issue.